2010
DOI: 10.1002/da.20674
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anxiety disorders and suicide attempts: findings from the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: Background-Previous work has suggested that anxiety disorders are associated with suicide attempts. However, many studies have been limited by lack of accounting for factors that could influence this relationship, notably personality disorders. The current study aims to examine the relationship between anxiety disorders and suicide attempts, accounting for important comorbidities, in a large nationally representative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
208
2
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(235 citation statements)
references
References 33 publications
15
208
2
10
Order By: Relevance
“…This relationship has been observed in other clinical populations (e.g., Campos et al, 2012Campos et al, , 2013Goldblatt, 2008;Lamis, et al, 2010;Nepon et al, 2010;Youssef et al, 2004) and in individuals bereaved by suicide, with other reports confirming that complicated grief and depression are related to suicidal ideation (Mitchell et al, 2005). Our findings reaffirm the need to intervene with individuals bereaved by suicide to reduce distress as well as suicidal ideation and risk.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This relationship has been observed in other clinical populations (e.g., Campos et al, 2012Campos et al, , 2013Goldblatt, 2008;Lamis, et al, 2010;Nepon et al, 2010;Youssef et al, 2004) and in individuals bereaved by suicide, with other reports confirming that complicated grief and depression are related to suicidal ideation (Mitchell et al, 2005). Our findings reaffirm the need to intervene with individuals bereaved by suicide to reduce distress as well as suicidal ideation and risk.…”
Section: Discussionsupporting
confidence: 89%
“…In the general population, suicidal ideation is related with psychiatric illness and depressive mood (Bae, Lee, Cho, Kim, Im, & Cho, 2013) and several empirical studies linked depression, anxiety, and hostility with suicidal ideation (e.g., Campos, Besser, & Blatt, 2012, 2013Goldblatt, 2008;Lamis et al, 2010;Nepon, Belik, Bolton, & Sareen, 2010;Youssef et al, 2004).…”
mentioning
confidence: 99%
“…A population-based longitudinal study in adults (Sareen et al 2005) indicated that a pre-existing anxiety disorder is an independent risk factor for the subsequent onset of suicidal ideation and attempt. An epidemiological study of the relationship between anxiety disorders and suicide attempts found that panic disorder was significantly associated with lifetime suicide attempts, over and above the association with psychiatric co-morbidity (Nepon et al 2010). However the association of panic disorder with suicidal behaviour may primarily explained by comorbidity with depressive disorders (Diaconu & Turecki 2007), and the influence of comorbidity on mediating suicidality has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in ages 14 to 17 years, having psychological intervention, having been involuntarily committed, or having a comorbidity were statistically significant. Previous research shows that some of these stressors are associated with SI and SA, including being bullied [10,11], having poor sleep patterns [12], having a comorbidity such as depression or anxiety [13], being of female gender [14], family factors, the presence of psychiatric illness, and substance abuse [15]. With all of these factors already linked to SI and SA, it is important to note that the associations hold true in the chronic pain population as well.…”
Section: Discussionmentioning
confidence: 99%